Resistência omótica, congelabilidade e fertilidade do sêmen de garanhões frente a diferentes crioprotetores - Medeiros, Antonio Sylvio Lopes de [UNESP] (2007)
The sperm osmotic stress induced by the cryprotectors during cryopreservation is an important factor involved on sperm viability. The present study aimed to study the viability and fertility after induction of osmotic stress using different amides and glycerol. Experment 1 aimmed to study the semen freezability of 27 stallions with the utilization of the cryoprotectors dimetilacetamida (DA), metilformamida (MF), dimetilformamida (DF) e glicerol (GL), the amidas based cryoprotectors were superior to glycerol in the ability to preserve pos thaw motility and membrane integrity (p<0,001). From these 27 stallions 9 were selected and classified with acceptable freezability and 12 as non acceptable freezabilty based on post thaw quality after frozen with GL. No differences were observe on total motility (TM), progressive motility (PM) and membrane integrity (MI) for the acceptable and non acceptable freezabilty groups. Four stallions with higher freezabilty were selected from the acceptable group and no differences between amides and glicerol were observed (p>0.05). From the non acceptable group 6 stallions with lower freezability were sellected, and amides were superior to GL for all post thaw evaluated parameters. (p<0,0001). On Experiment II, the same 10 stallions were used to evaluated the effect of the osmotic stress on the viability of fresh semen. The semen was incubated for 10 minuts in a 1 Molar solution of each studied cryoprotector. A significant decrease on total motility were observed after the incubation on the hypertonic solution (12,93l15,22d; 61,53l16,17b; 44,67l22,68c; 41,73l24,28c, DA, MF, DF e GL respective) when compared with the control group (81,4l9,15a). The lower motility was observed on the DA treatment. Also a higher decrease in the membrane integrity was observed in the solution of DA, MF, DF e GL (48,47l9,49bc, 49,20l8,47bc, 53,07l12,04b, 42,33l12,15c respectively) compared with control (61,87l13,62a).